Antiproliferative activity of (η6-arene)ruthenacarborane sandwich complexes against HCT116 and MCF7 cell lines12. Issue 36 (11th August 2017) - Gozzi, Marta; Schwarze, Benedikt; Sárosi, Menyhárt-Botond; Lönnecke, Peter; Drača, Dijana; Maksimović-Ivanić, Danijela; Mijatović, Sanja; Hey-Hawkins, Evamarie
Abstract : The [(η 6 -arene)RuC2 B9 H11 ] complexes (arene = p -cymene (2 ), biphenyl (3 ) and 1-Me-4-COOEt-C6 H4 (4 )) show cytotoxic activity and excellent selectivity towards specific tumour cells. Abstract : Three [(η 6 -arene)RuC2 B9 H11 ] complexes (arene = p -cymene (2 ), biphenyl (3 ) and 1-Me-4-COOEt-C6 H4 (4 )) were synthesised according to modified literature procedures and fully characterised.2–4 were found to be moderately active against two types of tumour cell lines (HCT116 and MCF7), with IC50 values in the low micromolar range. However, viability of normal, healthy cells (MRC-5 cell line, MLEC and mouse macrophages) was not affected by treatment with2–4, indicating high selectivity of the metallacarborane complexes towards tumour cell lines, compared to the unselective antitumour agent cisplatin and other potential Ru II drugs. Moreover, flow cytometric analysis suggested that4 induces cell death via a caspase-dependent apoptotic mechanism. DFT calculations of the frontier molecular orbitals showed that the HOMO–LUMO gap in2–4 is smaller than in the corresponding cyclopentadienyl complexes2-Cp–4-Cp ( e.g. 5.47 (2 ) vs. 6.31 eV (2-Cp )). In order to assess the stability of2–4, particularly the ruthenium–dicarbollide bond, energy decomposition analysis (EDA) of2–4, together with the respective cyclopentadienyl analogues2-Cp–4-Cp, was performed. EDA suggests that the ruthenium(ii )–dicarbollide bond in the three complexes is mostly ionic and far stronger than the ruthenium(ii )–arene bond.